Activation of the circAGFG1/miR-195-5p/PD-L1 axis induces lung injury in sepsis - Yang Bi; Rui Ding; Xinyan Liu; Yun He; Xukun Liu; Shouye Ma; Chaofan Wang; Zhongfa Zhang; Xuan Song (Human Cell, 2025)
Severe sepsis can escalate to acute lung injury (ALI), a critical condition with limited treatment options. Emerging research highlights the role of non-coding RNAs, including microRNAs (miRNAs) and circular RNAs (circRNAs), in regulating epithelial and immune cell responses in sepsis-induced ALI. This study delves into the circAGFG1/miR-195-5p/PD-L1 axis to elucidate its potential in this context. The conducted experiments using Th17 cells differentiated from CD4+ T cells isolated from human umbilical cord blood, co-cultured with transfected Calu-3 cells. The assessed cell viability, RNA, and protein expression levels under inflammatory stimuli. In addition, we collected bronchoalveolar lavage fluid and lung tissues from a cecal ligation and puncture mouse model. Quantification of RNA and protein expression of inflammatory and survival markers provided insights into the regulatory mechanisms involved. Peripheral blood samples from sepsis/ALI patients and healthy controls revealed that circAGFG1 expression is significantly downregulated, while miR-195-5p expression is upregulated in patients compared to healthy individuals. In both Calu-3 cells and induced Th17 cells, as well as in sepsis-induced ALI mouse models, the circAGFG1/miR-195-5p/PD-L1 axis was shown to regulate the expression of inflammatory cytokines, Th17 cell differentiation, and markers of epithelial cell survival. Results show the circAGFG1/miR-195-5p/PD-L1 axis plays a critical role in the pathogenesis of sepsis-induced ALI. Targeting this axis could present a novel therapeutic strategy for preventing ALI in sepsis and other conditions characterized by heightened lung inflammation. This research paves the way for new treatment approaches, offering hope for improved outcomes in patients suffering from severe sepsis and ALI. Graphical abstract

Cyclic tensile stress promotes osteogenic differentiation via upregulation of Piezo1 in human dental follicle stem cells - Binqing Xie; Xianyi He; Ye Guo; Jie Shen; Binbin Yang; Rui Cai; Junliang Chen; Yun He (Human Cell, 2024)

Hedgehog pathway is negatively regulated during the development of Drosophila melanogaster PheRS-m (Drosophila homologs gene of human FARS2) mutants - Lidangzhi Mo; Rui Li; Chunxia He; Qi Chen; Changwei Xu; Liangliang Shen; Kun Chen; Yuanming Wu (Human Cell, 2022)

MiR-100-5p inhibits osteogenic differentiation of human bone mesenchymal stromal cells by targeting TMEM135 - Rui Wang; Miao Zhang; Ying Hu; Juan He; Qiao Lin; Nianchun Peng (Human Cell, 2022)

CCL19 suppresses gastric cancer cell proliferation, migration, and invasion through the CCL19/CCR7/AIM2 pathway - Rui Zhou; Jun Sun; Chunping He; Chao Huang; Honggang Yu (Human Cell, 2020)

SNHG16 regulates invasion and migration of bladder cancer through induction of epithelial-to-mesenchymal transition - Wenwei Chen; Tao Jiang; Houping Mao; Rui Gao; Hua Zhang; Yanfeng He; Changyi Liu; Qin Chen (Human Cell, 2020)